Heterotypic protection induced by synthetic peptides corresponding to three serotypes of foot-and-mouth disease virus. - Doel, T R (1990)
Synthetic peptide vaccines of the general sequence Cys-Cys(200-213)-Pro-Pro-Ser-(141-158)-Pro-Cys-Gly, where the numbered residues refer to VP1 sequences of three different strains of foot-and-mouth disease virus, have been evaluated in cattle and guinea pigs. High levels of serotype-specific (homotypic) antiviral and antipeptide antibody were produced with each peptide. The A- and O-serotype peptides provided complete protection of guinea pigs against their respective virus challenges. The C-serotype peptide appeared to be less effective than the other peptides. In cross-protection studies (heterotypic) in guinea pigs, it was possible to protect A-serotype peptide-vaccinated animals against O-virus challenge and vice versa. Some heterotypic protection was also achieved with the C-serotype peptide. The heterotypic protection observed related more to the presence of cross-reactive antipeptide antibody than to neutralizing antibody.